The Analysis of Implementation of Foreign Language Improvement in the Front Office Department to Improving Service Quality and Room Sales Volume at the Angkasa Raya Hotel, Sidikalang City, Dairi Regency - Muhammad Zulfan (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
Language skills, especially in the field of tourism, must have good language skills and mastery. n order to improve services in the hotel industry, foreign language skills are needed in order to serve the wishes of tourists from abroad. Here the management must comply with the use of foreign languages ​​with training data or when recruiting employees as a foreign language becomes an obligation in the acceptance of hotel employees. his study the authors use quantitative research methods. With the method of observation, questionnaires, documentation, literature study with Spearman correlation analysis and descriptive statistics. The data were obtained through distributing questionnaires to respondents, then the answers were obtained from SPSS 16 with correlation analysis. And from the SPSS output, the coefficient figure was 0.673. The coefficient value in the above result is positive, namely, 0.673 so that the relationship between the two variables is unidirectional (type of unidirectional relationship). Thus it can be interpreted that the use of foreign languages ​​must be increased by training in order to increase the volume of room sales increases.